Effect of adipose‐derived exosome and exosomal miRNA on glycolipid metabolism. Issue 3 (18th September 2022) - Xie, Dadi; Li, Jing; Jiang, Pei; Xue, Xianzhong; Wu, Linlin
Abstract: Glucose and lipids are important nutrients because they provide enough energy for cell activity. However, the human body takes in too much glucose and lipids, will cause obesity, diabetes and some other metabolism diseases. Adipose tissue exerts crucial roles in regulating whole‐body energy metabolic through its storage and secretion function. Exosomes are a family of extracellular vesicles released by all cell types that aid in cell‐to‐cell signal transmission, resulting in alteration of target cell phenotype and activity, particularly, under pathological conditions. Exosomes deliver information between cells by carrying certain cargos, such as, RNA, microRNA (miRNA), lipids and protein. In particular, the adipose tissue‐derived miRNAs play an essential role in glycolipid metabolism. MiRNAs are intricately related to obesity, diabetes and other obesity‐related metabolic diseases. Different miRNAs exhibit differential expression across disease states, and particular exosomal miRNAs can act as informative biomarkers and therapeutic targets. Hence, here, we present an updated extensive review of the significance of adipose‐derived exosome and exosomal miRNA in the regulation of glucose and lipid metabolism. Abstract : Exosomes secreted by adipose tissue transfer miRNAs to insulin target tissues to regulate glycolipid metabolism. MiRNAs have emerged as key factors of metabolic homeostasis via regulation of insulin signaling, lipolysis, and inflammation. MiRNAs dysregulation in metabolic diseases, such as obesity, type 2 diabetes stresses their potential as therapeutic targets.